1990
DOI: 10.1038/bjc.1990.316
|View full text |Cite
|
Sign up to set email alerts
|

Serum oestrogen levels in postmenopausal women: comparison of American whites and Japanese in Japan

Abstract: Summary Serum oestrone (El), oestradiol (E2) and sex hormone binding globulin (SHBG) levels were studied in postmenopausal Japanese women in Japan (n = 91) and postmenopausal American white women (n = 38). The Japanese women were deliberately chosen to be from a rural agricultural area in order to get samples which represent as closely as possible the traditional Japanese 'lifestyle' that gave rise to the low rates of breast cancer in Japan. El levels were 47%, and E2 levels 36%, greater in the American women;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
63
1
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(72 citation statements)
references
References 10 publications
(13 reference statements)
4
63
1
3
Order By: Relevance
“…In post-menopausal women it has been found that American whites have oestradiol levels three times those of recent Asian migrants to Hawaii (Goldin et al, 1986). Similar results have been found in a comparison of rural Japanese women and white women living in southern California (Shimizu et al, 1990). These observations are consistent with the hypothesis that oestrogens play an important role in the aetiology of breast cancer.…”
Section: Discussionsupporting
confidence: 63%
“…In post-menopausal women it has been found that American whites have oestradiol levels three times those of recent Asian migrants to Hawaii (Goldin et al, 1986). Similar results have been found in a comparison of rural Japanese women and white women living in southern California (Shimizu et al, 1990). These observations are consistent with the hypothesis that oestrogens play an important role in the aetiology of breast cancer.…”
Section: Discussionsupporting
confidence: 63%
“…The low oestrogen levels of post-menopausal women living a traditional lifestyle in Japan (Shimizu et al, 1990) were not observed in the Japanese-American women we studied, most of whom (27 of 30) were born in the USA. Geometric mean plasma E1 levels were in fact highest in Japanese-American women, and their geometric mean plasma E2 levels were very close to those of Whites.…”
Section: Discussionmentioning
confidence: 92%
“…Studies of plasma oestrogen concentrations in 'traditional' Asians (living in Asia) compared with Whites have found lower concentrations in the Asians (Goldin et al, 1986;Key et al, 1990;Shimizu et al, 1990). In particular, a study of post-menopausal Japanese women in Miyagi and non-Latina White women in Southern California found a 32% lower level of plasma oestrone (E1) and a 27% lower level of plasma oestradiol (E2) in the Japanese women (Shimizu et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Genetic differences concerning important metabolic enzymes, for example, higher frequency of a variant allele of cytochrome P450 1A1 gene, were reported, 37 and endogenous estrogen levels and the number of estrogen receptors have been reported to differ between Japanese and Caucasians. 38,39 Thus, an association between smoking and breast cancer might appear more readily in Japanese. The incidence of breast cancer among premenopausal women (88/90,161 person-year) was almost the same as that among postmenopausal women (90/107,241 person-year), and the association observed in premenopausal women was strong.…”
Section: Discussionmentioning
confidence: 99%